2018
DOI: 10.1021/acs.jafc.8b01189
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Ameliorates High-Fat-Diet-Induced Non-alcoholic Fatty Liver Disease through Peroxisome Proliferator-Activated Receptor α-Mediated Activation of β Oxidation and Suppression of Inflammation

Abstract: Peroxisome proliferator-activated receptor α (PPARα) plays a protective role against non-alcoholic fatty liver disease (NAFLD). Sodium butyrate (NaB) has been shown to alleviate NAFLD, yet whether and how PPARα is involved in the action of NaB remains elusive. In this study, NaB administration alleviated high-fat-diet-induced NAFLD in adult rats, with a decrease of hepatic triglyceride content from 108.18 ± 5.77 to 81.34 ± 7.94 μg/mg ( p < 0.05), which was associated with a significant activation of PPARα. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 45 publications
0
60
1
Order By: Relevance
“…Zhou et al (2017a) reported that FMT attenuated high-fat diet-induced NASH in mice via beneficial regulation of gut microbiota. The administration of butyrate, a SCFA, effectively ameliorates lipid accumulation and liver inflammation in animal NAFLD models, through modulation of gut microbiota and gut barrier function (Zhou et al, 2017b), attenuation of inducible nitric oxide synthase (iNOS) induction (Jin et al, 2016), and suppression of inflammatory pathways (Sun et al, 2018). The effect of FMT on NAFLD/NASH is just beginning to be investigated and requires more animal and human clinical studies.…”
Section: The Microbiome As a Potential Therapeutic Target In Nafld Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (2017a) reported that FMT attenuated high-fat diet-induced NASH in mice via beneficial regulation of gut microbiota. The administration of butyrate, a SCFA, effectively ameliorates lipid accumulation and liver inflammation in animal NAFLD models, through modulation of gut microbiota and gut barrier function (Zhou et al, 2017b), attenuation of inducible nitric oxide synthase (iNOS) induction (Jin et al, 2016), and suppression of inflammatory pathways (Sun et al, 2018). The effect of FMT on NAFLD/NASH is just beginning to be investigated and requires more animal and human clinical studies.…”
Section: The Microbiome As a Potential Therapeutic Target In Nafld Anmentioning
confidence: 99%
“…Pharmaceuticals targeting bile acid dysregulation in NAFLD, including FXR agonists, PPARa agonists, ursodeoxycholic acid (UDCA), and its derivatives, have entered different phases of clinical trials, and some of them have shown promising therapeutic effects (Yu et al, 2018). The administration of butyrate, a SCFA, effectively ameliorates lipid accumulation and liver inflammation in animal NAFLD models, through modulation of gut microbiota and gut barrier function (Zhou et al, 2017b), attenuation of inducible nitric oxide synthase (iNOS) induction (Jin et al, 2016), and suppression of inflammatory pathways (Sun et al, 2018).…”
Section: The Microbiome As a Potential Therapeutic Target In Nafld Anmentioning
confidence: 99%
“…Recently, oral butyrate supplementation was reported to decrease cytokine release in patients with metabolic syndrome [13]. In addition, studies also suggest that an oral supplementation of therapeutic doses of sodium butyrate (SoB) (0.2-0.6 g/kg bw/d) may attenuate insulin resistance and the development of NAFLD, e.g., steatosis, inflammation and even early signs of fibrosis in rodents [6,[14][15][16]. In these studies, it was shown that the beneficial effects of SoB on the development of NAFLD are associated with protection against the induction of inducible nitric oxide synthase (iNOS) and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased uptake of circulating FA, increased hepatic lipogenesis, reduced rate of FA oxidation and reduced FA secretion are the multiple mechanisms that lead to an increased accumulation of lipids in the liver [36]. Studies have shown that butyrate restores PPARα activation in HFD fed rats, thus enhancing FA β-oxidation, inhibiting lipid synthesis and downregulating nuclear factor-kappa B pathways and inflammation [37][38]. In the current report, our data also showed that OVX mice with decreased butyrate content had upregulation of FA intake and synthesis but downregulation of oxidation related gene and protein expression.…”
Section: Discussionmentioning
confidence: 99%